Ergative and Antipassive Construction in Minangkabaunese: Are There? - Jufrizal, Jufrizal; Lely Refnita; M. Affandi Arianto (Linguistik Indonesia, 2024)
That Minangkabunese has active-passive dichotomy is not questioned anymore since it has been treated as an accusative language. Further typological analysis toward grammatical constructions of this language leads to a claim that it may be treated as an ergative language in which the ergative and antipassive constructions exist. That Minangkabaunese has ergative and antipassive construction is still questioned in some matters. Therefore, further grammatical-typological data, analysis, and discussion are needed. This paper, which is based on and developed from a part of results of research conducted in 2021-2022, particularly analyses whether Minangkabaunese has ergative and/or antipassive constructions. Two questions are raised, namely: (i) are there ergative and antipassive constructions in Minangkabaunese? and (ii) what is the linguistic implication of such claim toward grammatical typology of Minangkabaunese? This descriptive-qualitative study was practically operated as a linguistic field research and supported by a library study. Native speakers as represented by selected informants and written texts of Minangkabaunese were the sources of data. The data are in the form of clause constructions of Minangkabunese identified as the standard ones and were analyzed based on related theories of grammatical typology. The result of data analysis reveals that Minangkabaunese has ergative and antipassive constructions. Implicationally, this language may be typologically treated as an ergative language at the syntactic level beside as an accusative language.